Electrodes: A Combination of X‐Ray Tomography and Carbon Binder Modeling: Reconstructing the Three Phases of LiCoO2 Li‐Ion Battery Cathodes (Adv. Energy Mater. 8/2014). Issue 8 (June 2014) - Zielke, Lukas; Hutzenlaub, Tobias; Wheeler, Dean R.; Manke, Ingo; Arlt, Tobias; Paust, Nils; Zengerle, Roland; Thiele, Simon
<x xml:space="preserve">Abstract</x> Representative X‐ray tomography based models of LiCoO2 electrodes usually neglect the carbon binder domain (CBD). As reported by Simon Thiele and co‐workers in article number 1301617, this deficiency can be overcome by statistically modelling CBDs in the pore space of an active material X‐ray reconstruction. Their influence on electrical conductivity, tortuosity, and contact area are compared. In the image, the electrodes represent conductivity calculations, while the colored clusters represent large connected CBD agglomerates. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>